Goal Setting and Goal Striving in Consumer Behavior - Bagozzi, Richard P.; Dholakia, Utpal (Journal of Marketing, 1999)
Goals play an essential role in the purposive behavior of consumers, but scholars only recently have begun to examine the motivation for goals, their selection and modification, and their pursuit and attainment. One purpose of this article is to outline a conceptual framework for thinking about how goals emerge, influence decision making, and guide consumer choice and action. Another purpose is to integrate classic ideas proposed by consumer researchers with emerging concepts and models proposed by cognitive psychologists, social psychologists, and other social scientists. Finally, the authors’ aim is to present several new ideas on goal setting and goal striving and point out how they can enrich the study and practice of consumer behavior.